Strategi Komunikasi Pemasaran melalui Influencer pada Media Sosial Studi Akun Instagram @secondatebeauty - Kezia Therezia Marpaung; Roswita Oktavianti (Kiwari, 2023)
Secondate Beauty is a local cosmetic brand that launched a make up brand in 2020 in Indonesia. The owner of Secondate is a rising beauty influencer, namely Titan Tyra, while Gitta Amelia does bookkeeping in the world of Finance and Venture Capital which is more male-oriented. With the emergence of Secondate, Titan and Gitta hope that the products that are born can have value and want to create valuable products at affordable prices through social media, websites and e-commerce. Brand Activation is a form of marketing interaction between consumers and brands so that customers can know the brand carefully. The approach taken by Brand Activation is by introducing significant things through direct marketing activation, promotions activation, social media activation, sponsorship activation, marketing event activation which are aligned with the four main pillars of Brand Activation through product and service, employees, identity, and communication to understand that the role of influencers in Secondary beauty products is to promote products and present influencer marketing trends. This research aims to find out the Role of Influencers in Brand Activation through social media. The research data uses a qualitative approach with a descriptive case study research method to obtain data collection, namely interviews, observation and documentation using three informants with the object of research as Secondate Beauty. The results of this study state that Brand Activation activities also utilize social media through Influencers with promotions and social media that are displayed to the public. Secondate Beauty merupakan sebuah brand kosmetik lokal yang meluncurkan merek make up pada tahun 2020 di Indonesia. Pemilik Secondate merupakan beauty influencer yang sedang naik daun yaitu Titan Tyra sedangkan Gitta Amelia melakukan pembukuan di dunia Keuangan dan Modal Ventura yang lebih mengarah oleh pria. Dengan munculnya Secondate ini Titan dan Gitta berharap produk yang di lahirkan dapat memiliki nilai dan ingin mewujudkan produk yang bernilai dengan harga terjangkau melalui media sosial, website dan e-commerce. Brand Activation merupakan sebuah bentuk interaksi pemasaran antara konsumen dan brand sehingga pelanggan dapat mengetahui brand dengan seksama. Pendekatan yang dilakukan Brand Activation dengan cara memperkenalkan hal yang signifikan melalui direct marketing activation, promotions activation, social media activation, sponsorship activation, marketing event activation yang diselaraskan dengan empat pilar utama Brand Activation melalui product and service, employees, identity, dan communication untuk memahami bahwa peran influencer pada produk Secondate beauty guna mempromosikan produk dan menghadirkan trend influencers marketing. Penelitian ini ditujukan mengetahui bagaimana peran influencer dalam brand activation melalui media sosial. Data Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian studi kasus deskriptif memperoleh pengumpulan data yaitu wawancara, observasi dan dokumentasi dengan menggunakan tiga narasumber dengan objek penelitian Secondate Beauty. Hasil penelitian ini menyatakan bahwa kegiatan Brand Activation juga memanfaatkan media sosial melalui Influencer dengan promosi dan sosial media yang ditampilkan kepada khalayak.